Pharmacogenomic Insights Into The Response To Imatinib In Chronic Myeloid Leukaemia: The Role Of CYP3A4 Polymorphisms - Khan, Asma; Fatima, Urooj; Zaidi, Urooj; Munir, Attiya; Aslam, Hina (Journal of Rawalpindi Medical College, 2025)
Objective: To investigate the effect of CYP3A4 polymorphisms rs2740574 and rs2242480 on the response to Imatinib Mesylate in treatment-naïve patients with chronic myeloid leukaemia (CML). Methods: It was a prospective, non-interventional observational genetic association study involving 106 treatment-naive CML patients genotyped for rs2740574 and rs2242480. According to the Helsinki Declaration, the study was conducted in compliance with current good clinical practices and was approved by the Ethical Review Committee. Blood samples and clinical data were collected in the pathology department between March 2018 and March 2020. Informed consent was obtained from all participants. Treatment response was evaluated at 3 months based on complete hematologic response (CHR) and plasma Imatinib levels. Results: Patients with wild-type homozygous genotypes for both polymorphisms exhibited higher CHR rates (75% vs. 50% and 30% for rs2740574; 80% vs. 55% and 35% for rs2242480). Conclusions: CYP3A4 polymorphisms rs2740574 and rs2242480 predict Imatinib response. Early detection of non-responders based on polymorphism analysis before treatment initiation allows timely initiation of second-generation Tyrosine Kinase Inhibitors (e.g., dasatinib, nilotinib), thereby avoiding ineffective Imatinib therapy and facilitating earlier achievement of treatment-free remission. Keywords: Tyrosine Kinase Inhibitors, Leukaemia, Imatinib Mesylate, Cytochrome P-450 Cyp3A4, Pharmacogenetics